2021
DOI: 10.1021/acsami.1c08496
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the Mechanism of Condensation-Mediated Degradation of Organofunctional Silane Self-Assembled Monolayer Coatings

Abstract: Dropwise condensation is favorable for numerous industrial and heat/mass transfer applications due to the enhanced heat transfer performance that results from efficient condensate removal. Organofunctional silane self-assembled monolayer (SAM) coatings are one of the most common ultrathin low surface energy materials used to promote dropwise condensation of water vapors because of their minimal thermal resistance and scalable synthesis process. These SAM coatings typically degrade (i.e., condensation transitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 68 publications
0
29
0
Order By: Relevance
“…Although past work has conclusively demonstrated that silane monolayers are poor hydrophobic promoters for dropwise condensation due to the lack of durability, , they act as functional adhesion promoters. When a silane is directly exposed to water, it becomes chemically unstable and desorbs due to the hydrolysis reaction between its silanol group and water. , Past studies have experimentally demonstrated that a direct deposition of silane monolayers on metals results in rapid (within hours) degradation during steam condensation. , In our structure, having an additional polymer layer on top of the silane layer prevents direct contact between the water and silane, thus protecting the silane layer from reaction and desorption. Hence, we do not expect delamination to occur at the self-assembled monolayer (SAM)–substrate interfaces.…”
Section: Results and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Although past work has conclusively demonstrated that silane monolayers are poor hydrophobic promoters for dropwise condensation due to the lack of durability, , they act as functional adhesion promoters. When a silane is directly exposed to water, it becomes chemically unstable and desorbs due to the hydrolysis reaction between its silanol group and water. , Past studies have experimentally demonstrated that a direct deposition of silane monolayers on metals results in rapid (within hours) degradation during steam condensation. , In our structure, having an additional polymer layer on top of the silane layer prevents direct contact between the water and silane, thus protecting the silane layer from reaction and desorption. Hence, we do not expect delamination to occur at the self-assembled monolayer (SAM)–substrate interfaces.…”
Section: Results and Discussionmentioning
confidence: 85%
“…15,39−41 Past studies have experimentally demonstrated that a direct deposition of silane monolayers on metals results in rapid (within hours) degradation during steam condensation. 15,41 In our structure, having an additional polymer layer on top of the silane layer prevents direct contact between the water and silane, thus protecting the silane layer from reaction and desorption. Hence, we do not expect delamination to occur at the self-assembled monolayer (SAM)−substrate interfaces.…”
Section: Resultsmentioning
confidence: 99%
“…Hydrophobic and superhydrophobic surfaces have been a subject of active research for several decades as they present interest for both fundamental science and industry [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The water-repellent properties of materials are known to be either provided by their intrinsically low surface energy or by depositing a thin top-layer with low energy.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled ultrathin monolayers of organosilanes, which are one of the most commonly used low-surface energy coatings (often referred to as ‘hydrophobizers’), have been applied on metal, oxide, ceramic and Si substrates [ 1 , 8 , 14 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. For several decades, various organosilanes, including fluorinated alkylsilanes (FASs), have been used as hydrophobizing agents deposited either via immersion in liquid bath [ 1 , 8 , 14 , 21 , 26 , 27 , 32 , 33 , 34 , 35 ] or from gas phase [ 13 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation